Metformin use and cardiovascular outcomes in patients with diabetes and chronic kidney disease: a nationwide cohort study - Min-Ho Kim; Hyung Jung Oh; Soon Hyo Kwon; Jin Seok Jeon; Hyunjin Noh; Dong Cheol Han; Hyoungnae Kim; Dong-Ryeol Ryu (Kidney Research and Clinical Practice, 2021)
Background Metformin has recently been shown not to increase the risk of lactic acidosis in patients with chronic kidney disease (CKD). Thus, the criteria for metformin use in this population has expanded. However, the relationship between metformin use and clinical outcomes in CKD remains controversial. Methods This study considered data from 97,713 diabetes patients with an estimated glomerular filtration rate of <60 mL/min/1.73 m2. The primary outcome was major adverse cardiac and cerebrovascular events (MACCE), and the secondary outcomes were all-cause mortality and incident end-stage renal disease (ESRD). Results Metformin users had a significantly higher risk of MACCE than non-users (hazard ratio [HR], 1.20; 95% confidence interval [CI], 1.14–1.26; p < 0.001). However, metformin users had a lower risk of all-cause mortality (HR, 0.78; 95% CI, 0.74–0.81; p < 0.001) and ESRD (HR, 0.44; 95% CI, 0.42–0.47; p < 0.001) during follow-up than non-users did. The relationships between metformin use and clinical outcomes remained consistent in propensity score matching analyses and subgroup analyses of patients with adequate adherence to anti-diabetes medication. Conclusion Treatment with metformin was associated with an increased risk of MACCE in patients with diabetes and CKD. However, metformin users had a lower risk of all-cause mortality and ESRD during follow-up than non-users did. Therefore, metformin needs to be carefully used in patients with CKD.